Food Habits of Red Snapper Lutjanus malabaricus in Pinrang Waters - L Rapi, Nuraeni; Tri Hidayani, Mesalina; Djumanto, Djumanto; Murwantoko, Murwantoko; Alifia, Frida (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Pinrang Regency is included in the scope of Indonesian waters which has the potential to catch red snapper. Snapper is an export commodity that has a high market price with a selling value of around Rp. 70,000 / kg. The aim is to determine the size structure, gonad maturity and sex ratio. This research was conducted from March to July 2019 in the waters of Pinrang Regency. The observed aspects are size structure, gonad maturity and sex ratio. The results obtained as many as 532 fishes, of which 226 males and 306 females. The total length ranges from 19.5 to 69.5 cm with the sex ratio in a balanced state. Gonadal maturity is 36% under immature conditions and 64% are mature gonads. The size of the first time maturity is 29 cm in males and 37 cm in females.